ANALISA RUANG INTERAKSI SOSIAL PADA RUMAH PENGASAPAN IKAN BANDARHARJO KOTA SEMARANG - Setiawan dudi Prasetio (Prodi Arsitektur UNIVERSITAS KEBANGSAAN, 2024)
One method of fish processing is by smoking fish, which has developed since decades ago in Bandarharjo, North Semarang. In their daily lives, people and workers in this area interact with each other both indoors and outdoors. The interaction spaces in this area are created based on the fish smokers’ daily activities to support the smoking industry process. From the results of the literature review, the interaction spaces created in this area have not been carried out in deeper research. This research was conducted by using a quantitative descripritive method with search techniques on field observations and simulation analysis using Depthmaps software. From the analysis results, it was found that the interaction spaces in this area consist of both physical and non-physical interaction spaces. The non-physical interaction spaces include macro, messo and micro interaction spaces. The macro interaction space includes the relationship between groups in the spatial setting of the fish smoking area, the messo interaction space includes interactions between individuals and groups with the spatial setting of the transition space between the outside and inside, and the micro interaction room is the relationship between individuals in the spatial setting inside the building